Fault rupture propagation through soft soil covers - ΜΠΟΥΚΟΒΑΛΑΣ ΓΕΩΡΓΙΟΣ; ΛΟΥΚΙΔΗΣ ΔΗΜΗΤΡΙΟΣ; ΚΩΝΣΤΑΝΤΙΝΟΣ ΑΝΤΩΝΙΟΥ (Bulletin of the Geological Society of Greece, 2002)
The article presents the methodology and preliminary results from analytical simulations regarding fault rupture propagation through soft soil cover. The analyses employ the Finite Difference method for the numerical solution of boundary value problems, combined with appropriately chosen constitutive model for the shearing response of the soil cover, velocity time history for the rupture and boundary conditions. Analytical predictions are compared to field observations for an overall, qualitative as well as quantitative, evaluation of the methodology. In addition, results from an extensive parametric study are used for an initial definition of the basic design parameters in the vicinity of the fault trace and their possible range of variation.